Genomic and phylogenetic analysis of a community-acquired extended-spectrum β-lactamase-producing Escherichia coli ST429 strain recovered from a urinary tract infection. (September 2020) - Xu, Juan; Lin, Wenping; Chen, Yanmin; He, Fang
Abstract: Objectives: Escherichia coli is one of the most prevalent bacterial pathogens causing urinary tract infections (UTIs). The increasing dissemination of extended-spectrum β-lactamase (ESBL)-producing E. coli in the community renders clinical treatment difficult. Here we report the complete genome sequence of a bla CTX-M-15- carrying E. coli strain (EC28) isolated from a urine sample of a female outpatient with UTI. Methods: The whole genome sequence of E. coli strain EC28 was determined using both a MinION™ sequencer and an Illumina NovaSeq 6000 system. De novo hybrid assembly of the short Illumina reads and long MinION reads was performed using Unicycler. Multilocus sequence typing (MLST), antimicrobial resistance genes (ARGs), plasmid replicons and phylogenetic relationship were analysed using the BacWGSTdb database. Results: The genome sequence of E. coli strain EC28 consists of six contigs comprising 5260 133 bp, including one chromosome and five plasmids. According to MLST analysis, EC28 belongs to ST429. Six ARGs were identified, including bla CTX-M-15 located on a 63, 295-bp IncI2-type plasmid. Twenty-three phylogenetically related E. coli ST429 strains were identified in the NCBI GenBank database, none recovered from China. The closest relative was an isolate recovered from Japan in 2009 that differed by 146 cgMLST loci. Conclusion: Here we report the first complete genome sequence of an ESBL-producing E. coli ST429 strain isolated from the community in China. The genome sequence of EC28 can be used as a reference sequence for comparative analysis, including acquisition and mobilisation of bla CTX-M genes in community-acquired E. coli strains.